2020
DOI: 10.21203/rs.2.23151/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Dyslipidemia With Sudden Sensorineural Hearing Loss: A Retrospective Study

Abstract: Background: Blood lipid levels have been widely studied in patients with sudden sensorineural hearing loss (SSNHL), but it has been unclear whether dyslipidemia associates with SSNHL. Whether there is a simple and feasible blood lipid index to predict the onset of SSNHL remains to be found.Methods: This study reviewed 100 SSNHL patients and 100 healthy subjects who received relevant clinical examination in our hospital from June 1, 2015 to June 1, 2019. The demographic, clinical characteristics, lipid levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This condition will affect the flow of oxygenfilled blood to the auditory organ. 22 The results of the analysis of the study comparing 250 patients with SSNHL with 250 without SSNHL found that LDL-C and apo B levels (p≤0.05) were significantly higher in the case group than in the control group. However, this study did not find a significant difference (p>0.05) in other types of lipid profiles such as apo AI and HDL-C (23).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This condition will affect the flow of oxygenfilled blood to the auditory organ. 22 The results of the analysis of the study comparing 250 patients with SSNHL with 250 without SSNHL found that LDL-C and apo B levels (p≤0.05) were significantly higher in the case group than in the control group. However, this study did not find a significant difference (p>0.05) in other types of lipid profiles such as apo AI and HDL-C (23).…”
Section: Discussionmentioning
confidence: 96%
“…The apo AI and HDL-C concentrations were assessed as protective factors against sudden sensorineural hearing loss. 22 Low-density lipoprotein cholesterol (LDL-C) is a lipoprotein particle that carries cholesterol to tissue cells in the periphery. Before LDL-C particles enter the blood vessel wall through endothelial cells, LDL-C will be oxidized in the subendothelial tissue into oxidized LDL-C (ox-LDL-C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations